Association of Helicobacter pylori Infection and Risk of Dyslipidemia: A Systematic Review and Meta‐Analysis - Ankita Gaonkar; Quazi Syed Zahiruddin; Muhammed Shabil; Soumya V. Menon; Mandeep Kaur; Mukesh Kumari; Puneet Sudan; K. Satyam Naidu; Shailendra Thapliyal; Jyoti Uikey; Rachna Kathuria; Sanjay Singh Chauhan; et al. (JGH Open)
ABSTRACT Background Although Helicobacter pylori (H. pylori) infections are widespread throughout the world, it is yet unknown whether they are linked to systemic illnesses like dyslipidemia. The purpose of this systematic review and meta‐analysis was to examine the connection between lipid metabolism and H. pylori infection, with a particular emphasis on how it affects dyslipidemia. Methods We conducted a thorough search up until October 10, 2024, across databases such as PubMed, Web of Science, and Embase. Studies that reported lipid profiles in both H. pylori‐infected and non‐infected patients were considered eligible. The primary outcomes were triglyceride, LDL‐C, HDL‐C, and total cholesterol levels, which were examined using a random‐effects model in R software version 4.4. Results There were 17 studies with more than 150,000 participants from 681 screened publications. Higher levels of LDL (MD: 5.32 mg/dL; 95% CI: 1.315 to 9.319) and total cholesterol (MD: 6.28 mg/dL; 95% CI: 0.718 to 11.842), as well as lower levels of HDL (MD: −2.06 mg/dL; 95% CI: −3.212 to −0.915), were the results of the meta‐analysis. Among those infected, triglyceride levels were likewise higher (MD: 7.93 mg/dL; 95% CI: 0.413 to 15.436), but the odds ratio (OR) did not show a significant increase in risk (OR: 1.002; 95% CI: 0.995 to 1.010). Conclusion H. pylori infection is associated with significant dyslipidemia, suggesting a potential link between chronic bacterial infection and lipid metabolism. The findings emphasize the need for further research to explore the mechanisms and potential therapeutic interventions.